Mentalcare: game-based learning on mental health awareness / Muhammad Aiman Zulkiffli, Mohd Nabil Zulhemay and Mohd Shukor Abd Rahman - Zulkiffli, Muhammad Aiman; Zulhemay, Mohd Nabil; Abd Rahman, Mohd Shukor (College of Computing, Informatics, and Mathematics, 2024)
Mental health awareness is important to understanding and supporting individuals with a range of mental health conditions. According to previous studies and preliminary studies that have been done, most people lack awareness of mental health. People often ignore mental health problems due to lack of exposure and the information available online is too boring for them to read every single one. Therefore, this project has developed MentalCare: Game- Based learning on mental health awareness. The objectives of this project are, 1) to design a storyboard about the importance of mindfulness in maintaining mental health, 2) to develop a 2D video game with a game-based learning concept to raise awareness about mental health care among the Malaysian community, 3) to evaluate the user enjoyment on the developed game-based learning application. The game was implemented Agile as a project methodology. The evaluation scale adapted is based on EGameFlow Model which consist of five dimensions: Concentration, Goal Clarity, Feedback, Immersion and Knowledge Improvement. The project findings indicated that the user agreed they had experience about 80% of element enjoyment in this game.